PPARγ S273 Phosphorylation Modifies the Dynamics of Coregulator Proteins Recruitment - Dias, Marieli Mariano Gonçalves; Batista, Fernanda Aparecida Heleno; Tittanegro, Thais Helena; de Oliveira, André Gustavo; Le Maire, Albane; Torres, Felipe Rafael; Filho, Helder Veras Ribeiro; Silveira, Leonardo Reis; Figueira, Ana Carolina Migliorini (Frontiers in Endocrinology, 2020)
Abstract The nuclear receptor PPARγ is essential to maintain whole-body glucose homeostasis and insulin sensitivity, acting as a master regulator of adipogenesis, lipid and glucose metabolism. Its activation through natural or synthetic ligands induces to the recruitment of coactivators, leading to transcription of target genes such as cytokines and hormones. More recently, post translational modifications, as PPARγ phosphorylation at Ser273 by CDK5 in adipose tissue, have been linked to insulin resistance trough the deregulation of expression of a specific subset of genes. Here, we investigate how this phosphorylation may disturb the interaction between PPARγ and some coregulator proteins as a new mechanism that may leads to insulin resistance. Through cellular and in vitro assays, we show that PPARγ phosphorylation inhibition increased the activation of the receptor, therefore the increased recruitment of PGC1-α and TIF2 coactivators, whilst decreases the interaction with SMRT and NCoR corepressors. Moreover, our results show a shift in the coregulators interaction domains preferences, suggesting additional interaction interfaces formed between the phosphorylated PPARγ and some coregulator proteins. Also, we observed that the CDK5 presence disturb the PPARγ-coregulator’s synergy, decreasing interaction with PGC1-α, TIF2 and NCoR, but increasing coupling of SMRT. Finally, we conclude that the insulin resistance provoked by PPARγ phosphorylation is linked to a differential coregulators recruitment, which may promote dysregulation in gene expression.